2024
DOI: 10.3390/mi15040438
|View full text |Cite
|
Sign up to set email alerts
|

Control of Self-Winding Microrobot Using an Electromagnetic Drive System: Integration of Movable Electromagnetic Coil and Permanent Magnet

Hao Li,
Zhaopeng Zhang,
Xin Yi
et al.

Abstract: Achieving precise control over the motion position and attitude direction of magnetic microrobots remains a challenging task in the realm of microrobotics. To address this challenge, our research team has successfully implemented synchronized control of a microrobot’s motion position and attitude direction through the integration of electromagnetic coils and permanent magnets. The whole drive system consists of two components. Firstly, a stepper motor propels the delta structure, altering the position of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ]. Additionally, research conducted in [ 14 , 15 , 16 , 47 ] demonstrated the utilization of a multi-solenoid system to energize magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ]. Additionally, research conducted in [ 14 , 15 , 16 , 47 ] demonstrated the utilization of a multi-solenoid system to energize magnetic fields.…”
Section: Introductionmentioning
confidence: 99%